Integrated conflict management design workbook : كتاب التصميم المتكامل لإدارة الخلافات (Arabic) - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2016)
Mediation Series is a set of three guides that will help policy-makers, organizations and practitioners build mediation practice and culture. The Series include Mediation Essentials, Integrated Conflict Management Design Workbook, and Making Mediation Law. Mediation Essentials serves as a complete orientation guide to ADR in general and to mediation. Making Mediation Law offers a robust perspective on how to design mediation policy and legislation. Guidance in this area is in high demand and scarce (besides the UNCITRAL Model Law on International Commercial Conciliation and its Guide, there aren’t many other comprehensive resources). We hope that Making Mediation Law will effectively fill that gap. Integrated Conflict Management Design Workbook offers a hands-on focus for designing effective dispute management systems for organizations.